The Equivalence of Definitions of the Natural Logarithm Function. (27th May 2022) - Ricardo, Henry
Summary: There are four definitions of the natural logarithm function commonly found in analysis texts: the inverse of the natural exponential, an integral, a limit, and the unique continuous solution of a functional equation. This article provides historical and pedagogical comments about each and establishes the equivalence of these four definitions.